Prediction and effect on relapse of natural killer cell alloreactivity based on KIR-HLA interactions in pediatric haploidentical transplantation with anti-thymoglobulin - Tang, Xiang-Feng; Luo, Yan-Hui; Si, Ying-Jian; Qin, Mao-Quan; Lu, Wei; Chen, Wei; Xing, Guo-Sheng; Cao, Wei; Zhou, Hai-Fei; Liu, Xiang-Jun (Frontiers in Immunology, 2025)
IntroductionRelapse continues to be a major factor contributing to therapeutic failure in haploidentical hematopoietic stem cell transplantation (HSCT). The role of natural killer (NK) cell alloreactivity mediated by killer immunoglobulin-like receptors (KIRs) is considered important in postoperative immune reconstitution and in mitigating relapse. However, its clinical implications remain incompletely defined, and its impact on allogeneic HSCT is controversial across studies.MethodsIn the present investigation, we assessed the effect of predicted NK cell alloreactivity through KIR–ligand interactions on relapse and survival outcomes in a pediatric cohort. This retrospective study included pediatric patients who underwent their first haploidentical HSCT following the Beijing protocol between 2013 and 2023. Both low- and high-resolution typing methods were employed for all donor and patient samples. The presence of NK cell alloreactivity was determined using predictive models incorporating the HLA class I molecules of both donors and recipients. NK cell alloreactivity was classified as ALLO or Non-ALLO based on the presence or absence of predicted alloreactivity, and its effects on relapse and overall survival were evaluated through individual and combinatorial interactions.ResultsMultivariate analysis demonstrated that, among patients lacking A3/A11, those who received grafts from donors with both KIR3DL2+ and A3/A11+ had an 86% lower risk of relapse (adjusted hazard ratio 0.136; p = 0.0489). Both Synthesis-iKIR and combined Synthesis-iKIR/KIR2DS1 showed significant independent effects on overall survival, with clinically adjusted hazard ratios of 0.305 and 0.316 (p < 0.005), respectively. The disease state at transplantation was an independent clinical factor influencing prognosis. Other additive models failed to effectively predict clinical outcomes in pediatric recipients.DiscussionThese results indicate that pediatric patients exhibiting NK cell alloreactivity, as predicted by the KIR3DL2–A3/A11 combination, had a significantly lower cumulative incidence of relapse. Furthermore, alloreactivity predicted by Synthesis-iKIR was significantly associated with improved overall survival. These findings have not been previously validated in pediatric studies and may have clinical relevance for haploidentical transplantation population, pending confirmation in larger cohorts.